Nutrient Omission in Corn Plant Development Cultivated in Nutrient Solution - Siqueira Dias Junior, Eduardo; de Oliveira Wesgueber, Nataly; da Silva, Cassia Milena; da Silva, Amanda Lídia; dos Reis André, Gabriel; Resende Rodrigues, Diego; Kölln, Oriel Tiago (Revista Ceres, 2025)
Correções do artigo publicado anteriormente.